VALUE ADDED MODEL OF COCONUT PROCESSING INDUSTRY (CASE STUDY) - Nurfajriah zhia; Halim Mahfud; Rudhy Ho Purabaya (Center for Study and Journal Management FTI UMI, 2021)
Coconut commodity has a strategic value because it has an important role in the economy, society and culture of Indonesian society. Coconut plant is a multipurpose plant where all parts of the plant have economic value, one of which is coconut husk. The potential of coconut coir is very large and has not been used optimally. Whereas coconut coir, when processed, will produce various products such as home industries, furniture, geotextiles, boards, and creative industries. This study is aimed at analyzing the potential development of the coconut coir processing industry and the added value that will be generated using the case study method and the location selection is done deliberately (purposive sampling). The business financial feasibility model obtained is a predictive model for analysis and planning of business financial feasibility through the NPV, IRR, PBP, BCR criteria with various scenarios of changes in prices, interest rates, and production scale.The business balance model obtained is a predictive model that can be used to analyze the price gap level to plan the price level that will provide proportional profit to produce coconut coir processing factory business. Based on the results of the verification of the model with input using the assumption of parameter values, it shows that the coconut coir processing industry is feasible to run.